2005
DOI: 10.2337/diabetes.54.11.3065
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Insulin Secretion

Abstract: The ATP-sensitive K ؉ channel (K ATP channel) senses metabolic changes in the pancreatic ␤-cell, thereby coupling metabolism to electrical activity and ultimately to insulin secretion. When K ATP channels open, ␤-cells hyperpolarize and insulin secretion is suppressed. The prediction that K ATP channel "overactivity" should cause a diabetic state due to undersecretion of insulin has been dramatically borne out by recent genetic studies implicating "activating" mutations in the Kir6.2 subunit of K ATP channel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
105
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 99 publications
4
105
0
1
Order By: Relevance
“…Conversely, gain-of-function mutations of Kir6.2 or SUR1 are expected to cause an undersecreting phenotype and hypoinsulinaemia. Consistent with this expectation, activating mutations cause both permanent and transient neonatal diabetes in mice and humans [13,14].…”
supporting
confidence: 55%
“…Conversely, gain-of-function mutations of Kir6.2 or SUR1 are expected to cause an undersecreting phenotype and hypoinsulinaemia. Consistent with this expectation, activating mutations cause both permanent and transient neonatal diabetes in mice and humans [13,14].…”
supporting
confidence: 55%
“…Therefore, penetrance of dominant mutations and variability in their clinical expressivity may also be explained by the influence of other genetic determinants and epistasis effects, by behavioral factors such as physical activity, body composition, and age on the clinical phenotype, as seen in other monogenic subtypes of diabetes (23). The functional properties of the new SUR1 mutations on electrophysiological parameters of the K ATP channel may give a valuable estimate on their pathological impact, although it may be difficult to demonstrate an effect such as in the case of the E23K polymorphism of the Kir6.2 subunit of the K ATP channel (24).…”
Section: Discussionmentioning
confidence: 99%
“…A persistent hyperexcitabilty of the ␤-cell results in unregulated insulin release and underlies hyperinsulinism with hypoglycemia in humans (1). Conversely, it is now clear that hypoexcitability can suppress insulin release and contribute to the converse disorder of diabetes (2).…”
mentioning
confidence: 99%
“…A clear picture is now emerging from both animal and human studies that such K ATP mutations can cause hyposecretion and underlie diabetes (2). Genetic studies have now identified mutations in the pore-forming Kir6.2 subunit of K ATP (KCNJ11) as a common cause of neonatal diabetes mellitus (NDM) in humans (3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
See 1 more Smart Citation